An integrated approach to the evaluation of patients with asymptomatic or minimally symptomatic hyperCKemia. Issue 1 (8th November 2021) - Gemelli, Chiara; Traverso, Monica; Trevisan, Lucia; Fabbri, Sabrina; Scarsi, Elena; Carlini, Barbara; Prada, Valeria; Mongini, Tiziana; Ruggiero, Lucia; Patrone, Serena; Gallone, Salvatore; Iodice, Rosa; et al.
Abstract: Introduction/Aims: Currently, there are no straightforward guidelines for the clinical and diagnostic management of hyperCKemia, a frequent and nonspecific presentation in muscle diseases. Therefore, we aimed to describe our diagnostic workflow for evaluating patients with this condition. Methods: We selected 83 asymptomatic or minimally symptomatic patients with persistent hyperCKemia for participation in this Italian multicenter study. Patients with facial involvement and distal or congenital myopathies were excluded, as were patients with suspected inflammatory myopathies or predominant respiratory or cardiac involvement. All patients underwent a neurological examination and nerve conduction and electromyography studies. The first step of the investigation included a screening for Pompe disease. We then evaluated the patients for myotonic dystrophy type II–related CCTG expansion and excluded patients with copy number variations in the DMD gene. Subsequently, the undiagnosed patients were investigated using a target gene panel that included 20 genes associated with isolated hyperCKemia. Results: Using this approach, we established a definitive diagnosis in one third of the patients. The detection rate was higher in patients with severe hyperCKemia and abnormal electromyographic findings. Discussion: We have described our diagnostic workflow for isolated hyperCKemia, which is based on electrodiagnostic data, biochemical screening, and first‐line genetic investigations, followed by successive targeted sequencing panels. Both clinical signs and electromyographic abnormalities are associated with increased diagnostic yields.